Pediatric Dentistry A Comprehensive Guide - Singh Virdi, Mandeep (IntechOpen, 2023)
As a parent, guardian, or healthcare provider, ensuring the oral health of children is a vital aspect of overall health and well-being. Pediatric Dentistry - A Comprehensive Guide is an insightful book that covers critical concepts and clinical studies in pediatric dentistry to provide a comprehensive understanding of oral health in children. Chapters address such topics as the "dental home" concept, which involves early dental visits and establishing a dental home for children to prevent oral health issues, stomatognathic dysfunction, the role of the community in promoting good oral health in children, the effects of malnutrition on pediatric oral health, and the role of metals in pediatric oral health. The book is a valuable resource for pediatric dentists, dental hygienists, and other healthcare providers interested in promoting and maintaining oral health in children. It also serves as a guide for parents and guardians seeking to ensure optimal oral health for their children.